An Analysis of Students’ Speaking Anxiety of XI KC Grade Students of SMKN 3 Bengkulu City - Yulita Minha (Edu-Ling: Journal of English Education and Linguistics, 2018)
The type of this research is Descriptive Qualitative research. It is aimed to find out the cause of students’ problem in speaking English, student’anxiety. The subjects of this study are 21 students of Second Grade KC 1 SMKN 3 Bengkulu City. In this research, the researcher collected the data by using data rubric of English student presentation assessment and Questionnaire. Then, there were several steps in the procedure of data analysis which was known as finding the data, analyze the data and conclude the conclusion and suggestion. According to matrix table that the researcher used to analyze the students speaking skill in pronunciation, intonation, fluency, content, and average level of speaking, the researcher got the result that showed the speaking skill of the students in second grade KC1 SMKN 3 Bengkulu City is on medium level. From the questionnaire, this result showed that there are six reasons why the students are not anxious to speak English, such as lack of familiarity with the task, fear of making mistakes, low motivation, input that can not be understood, lack of confidence, low English ability. So that, the researcher gave a suggestion to solve that problem, such as looking for friends, preparation, relaxation, think positive and resignation.